Analisis Kepuasan Pengguna Katalog Induk Nasional Online Perpustakaan Nasional RI - tritawirasta, wiratna; ardiansyah, Firman; Yulia, Yuyu (Jurnal Perpustakaan Pertanian, 2012)
Analysis of User Satisfaction on Online Union Catalogof National Library of IndonesiaABSTRACTInternational Standard Organization (ISO) Technical Report (TR) -28118 in 2009 item A.2 mentioned that the national library of acountry should publish national bibliographies in a catalog as soonas in line with the publication of a new collection in the country. Itcan only be possible if the catalog is in electronic form, known asonline catalog. National Library of Indonesia has developed anonline union catalog (http://kin.pnri.go.id) since 2008. However, itshowed very low utilization. A study has been carried out to analyzeuser satisfaction on online union catalog based on user perception.The research method is a survey using a questionnaire containing 37questions. Data were collected in 33 provincial library institutionsinvolving users and the librarians. Measurement of the level of usersatisfaction was based on ISO 9241-11: Guidance on Usability. Thestudy results showed that the existence, use and understanding ofonline union catalog meets the basic needs of users and librarians onsearching information. Copy cataloging function in online unioncatalog has not yet used optimally. Over 80% of respondents respondedpositively to the improvement of features of online union catalog 2.0.